Hospital-based Retrospective Study of Cryptococcal Meningitis in a Large Cohort from India - Naik, Karkal Ravishankar (Ann Indian Acad Neurol, 2017)
BACKGROUND: Cryptococcal meningitis is an important and a fatal neuroinfection. Early diagnosis and treatment is of utmost importance in reducing morbidity and mortality. MATERIALS AND METHODS: Data of patients with laboratory-confirmed cryptococcal meningitis seen in tertiary care hospital were reviewed. Details of demographic profile, clinical data, laboratory parameters, complications, and in-hospital mortality were studied. RESULTS: Among 97 patients with cryptococcal meningitis (79 men, 18 women), 88 were HIV-positive, two were diabetic, and seven were sporadic. Their age ranged from 23 to 67 years (39.16 ± 9.49). Additional pathogens for meningitis were identified in 24 patients. Headache was the most common symptom (91%) followed by fever (66%), vomiting (51%), altered sensorium (31%), and seizures (20%). Neurological deficits included cranial nerve palsies (28), motor deficits (11), sphincter disturbances (5), and sensory involvement in four patients. Complications included renal dysfunction (20%), dyselectrolytemia (20%), seizures (16%), hypersensitivity (7%), and hepatic dysfunction (5%). Favorable outcome was seen in 72 patients, 13 remained unchanged, and 12 died. Rapid clinical progression, low cerebrospinal fluid (CSF) cell count and protein were associated with higher mortality. CSF cell count and protein were lower in patients who had isolated cryptococcal meningitis compared to those with additional pathogen. Mean sugar levels were higher and duration of illness was shorter in HIV-negative individuals. CONCLUSION: Cryptococcal meningitis is common in patients with AIDS. Effective and early antifungal treatment carries a good prognosis. On rapid evolution of the disease, decreased CSF cell count and protein heralds poor prognosis and warrants initiation of early specific treatment.